2 la puterea x-3=1
3 la puterea x+1=3 • 3 la puterea x
6 la puterea x+8=36 • 6 la puterea 2x
2 la puterea x+7=2 la puterea x • 2 la puterea x+1
Răspunsuri la întrebare
Răspuns de
1
2ˣ - 3 = 1
2ˣ = 1 + 3
2 ˣ = 4
2ˣ = 2² ==> x = 2
_________________________
3ˣ⁺¹ = 3 x 3ˣ
3ˣ x 3 = 3 x 3ˣ ==> ∀ x ∈N; R
6ˣ⁺⁸ = 36 x 6²ˣ
6ˣ⁺⁸ = 6²ˣ ⁺ ² ===> x + 8 = 2 x + 2 => 2 x - x = 8 - 2 => x = 6
__________________________________________________
2ˣ ⁺⁷ = 2ˣ x 2ˣ⁺¹ = 2²ˣ ⁺¹ = > 2 x + 1 = x + 7 ==> 2 x - x = 7 - 1 => x = 6
Alte întrebări interesante
Limba română,
8 ani în urmă
Engleza,
8 ani în urmă
Biologie,
8 ani în urmă
Matematică,
9 ani în urmă
Engleza,
9 ani în urmă
Matematică,
9 ani în urmă
Matematică,
9 ani în urmă
Istorie,
9 ani în urmă